Ephesians: an introduction and study guide : being a Christian at home and in the cosmos - Fowl, Stephen E. (T & T Clark study guides to the New Testament, 2017)
Arguments of Ephesians -- Questions of authorship, history and literary relations -- Distinctly Ephesian -- Reading closely -- Another type of close reading